Implementation of Problem-Based Learning with Green Chemistry Vision to Improve Creative Thinking Skill and Students’ Creative Actions (Jurnal Pendidikan IPA Indonesia, 2017)
The aims of the research are to increase creative thinking skills and creative action through the implementation of Problem-Based Learning (PBL) model with green chemistry insight. The research design of mixed method experimental models embedded with a pretest-posttest control group was applied to measure the effectiveness of the application of the of Problem-Based Learning (PBL) model with green chemistry insight at the end of the learning activities to increase creative thinking skills and creative action of students in solving various environmental problems. The results showed that creative thinking before and after implementation of the experimental class is 82.42 and N-Gain 0.73 (high category), while that in the control class is 69.85 and N-Gain 0.32 (medium category). The assessment of the creative action begins from investigating groups of problem-solving ideas written on the outcome of the discussion groups. The consultation with the lecturer is carried out for the implementation of tasks, exhibit, communication (presentation), and rewriting in the form of reports in more detail results/ products of the creative activity that has been done and also the sustainability of the action. The application of the Problem-Based Learning (PBL) model with green chemistry insight is able to increase creative thinking skills and creative action of the students.